Incrassamarin A–D: Four new 4-substituted coumarins from Calophyllum incrassatum and their biological activities - Aminudin, Nurul Iman; Ahmad, Farediah; Bakhtiar, M. Taher; Mohamed Zulkifli, Razauden (Elsevier, 2016)
Four new 4-substituted coumarins, incrassamarin A (1), B (2), C (3) and D (4) with (7S,8S)-7,8-dihydro-5- hydroxy-7,8-dimethyl-4-propyl-2H,6H-benzo[1,2-b;5,4-b’]dipyran-2,6-dione (5), friedelin, carpachromene, amentoflavone, epiafzelechin and L-quercitrin were isolated from the barks and leaves of Calophyllum incrassatum (Guttiferae). The compounds were isolated and purified by size-exclusion recycling HPLC and column chromatographic techniques. The structures of the compounds were determined by spectroscopic means. The compounds were tested for their cytotoxic activity towards MCF-7 and A-549 cell lines and a-glucosidase enzymatic inhibitory activity. Compound (1) displayed cytotoxic activity against A-549 cell lines with IC50 87.71mg/mL and showed inhibition towards a-glucosidase enzymatic activity with IC50 93.25mM. This is the first report on the isolation of phytochemicals from the barks and leaves of C. incrassatum and their bioactivities.